Pertumbuhan Acacia auriculiformis sampai Umur Enam Bulan pada Berbagai Dosis Pupuk Kandang di Pantai Glagah Kabupaten Kulonprogo Daerah Istimewa Yogyakarta. - , MEDINA ARIANA; , Ir. Sukirno Dwiasmoro prianto, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia has vast coastline more than 95.181 km, other than the potential of producing land for agriculture, work place and cultivation of wood plants. Glagah Beach areas are critical land so that rehabilitation is needed and erosion control is one of the ways to plant plants that are appropriate for that type of land. The plant Acacia auriculiformis ecologically has benefits for beach lands. To fulfill the success of the growing plants in the field, therefore fertilizing the plants is needed. The intention of this research is to know the effects of fertilizers and to know the most appropriate dosage of fertilizers towards the growth of A. auriculiformis in the beach areas. This research was conducted at Glagah beach, in the village of Karangwuni, Wates, Yogyakarta. It was also conducted at the Soil Laboratory of Gadjah Mada University for 6 months, starting from January to June 2011. This research is using Randomized Complete Block Design with the factorial trial. The factors used were the dosage of manure fertilizer which consisted of 4 levels which are